Variations and Methodological Components in CEFR-Aligned Language Tests: A Systematic Review - Nik Aloesnita, Nik Mohd Alwi; Wan Alisa Hanis, Wan Abdul Halim (Universiti Teknologi MARA Kedah, 2024)
The Common European Framework of Reference for Languages (CEFR) has provided a flexible framework for constructing and implementing language tests. Its flexibility has led to the development of various CEFR-aligned language tests that attempted to conform to its framework. The variability in test purpose, quality, and difficulty has necessitated the use of different methodological decisions when conducting studies on CEFR-aligned language tests. The current study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to conduct a present systematic review. A total of 31 journal articles on CEFR-aligned language tests were used to explore the methods employed in the articles. The review identified six prominent discoveries: the study method, data analysis, participant characteristics, rater participation, number of essays, and writing genres. The current study revealed the prevalence of quantitative methods, the focus on specific participant characteristics, the inclusion of many raters and essays, and the inclination towards two dominant writing genres in studies on CEFR-aligned language tests. By discovering the shared methodological components adopted in current CEFR-aligned language studies, this study guides researchers and practitioners in enhancing the validity, reliability, and generalisability of studies on CEFR-aligned language tests in various contexts through successful replicability.